Crassostrea gigas - Araya, Juan Francisco (Zenodo, 2015)
Crassostrea gigas (Thunberg, 1793) Description Osorio (2002), Coan and Valentich-Scott (2012). Distribution Native to Japan and Korea and the North Atlantic Ocean (Coan and Valentich- Scott 2012). This species is usually introduced through aquaculture (Diederich et al. 2005). In Chile this species was introduced in 1978 and has been recorded from latitude 15° S to 40° S (Valdovinos 1999). Possible mechanism of introduction/Status Intentional transplantation/unestablished (Valdovinos 1999). Remarks Filter feeder, invasive species, species of commercial importance (Diederich et al. 2005). UA, II. : Published as part of Araya, Juan Francisco, 2015, Current status of the non-indigenous molluscs in Chile, with the first record of Otala punctata (Müller, 1774) (Gastropoda: Helicidae) in the country and new records for Cornu aspersum (Müller, 1774) and Deroceras laeve (Müller, 1774), pp. 1731-1761 in Journal of Natural History 49 (29) on page 1734, DOI: 10.1080/00222933.2015.1006703, http://zenodo.org/record/3997965 : {"references": ["Thunberg CP. 1793. Tekning och Beskrifning pa en stor Ostronsort ifran Japan. K Sven Vetensk Akad Handl. 14: 140 - 142.", "Osorio C. 2002. Moluscos marinos en Chile: especies de importancia economica: guia para su identificacion. Santiago, Chile: Facultad de Ciencias, Universidad de Chile.", "Coan EV, Valentich-Scott P. 2012. Bivalve seashells of tropical West America. Marine bivalve mollusks from Baja California to northern Peru. Santa Barbara Monographs: Santa Barbara Museum of Natural History.", "Diederich S, Nehls G, Beusekom JE, Reise K. 2005. Introduced Pacific oysters (Crassostrea gigas) in the northern Wadden Sea: invasion accelerated by warm summers? Helgoland Mar Res. 59: 97 - 106.", "Valdovinos C. 1999. Biodiversidad de moluscos chilenos: base de datos taxonomica y distribucional. Gayana. 63: 111 - 164."]}